Emergence of a Novel Recombinant Pseudorabies Virus Derived From the Field Virus and Its Attenuated Vaccine in China - Tan, Lei; Yao, Jun; Lei, Lei; Xu, Kaiwen; Liao, Fan; Yang, Shibiao; Yang, Lincheng; Shu, Xianghua; Duan, Deyong; Wang, Aibing (Frontiers in Veterinary Science, 2022)
The occurrence of pseudorabies (PR) caused by pseudorabies virus (PRV) causes huge economic losses to pig industry in China. Moreover, the potential threat of PRV to humans’ heath has received wide attention recently. The prevalence of two PRV genotypes and application of their corresponding live attenuated vaccines increase the recombination possibility. In the present study, a novel recombinant PRV strain designed as HN-2019 was isolated from one sick piglet in Hunan province, China, its genetic features and pathogenicity were further investigated. The results showed that the glycoprotein gE and gG genes of HN-2019 strain displayed higher nucleotide homology with PRV classical strains (such as Ea and Fa) compared to others. However, its TK gene with continuous nucleotide deletions shared 100% nucleotide identify with HB-98 vaccine strain, which was derived from Ea strain. Moreover, HN-2019 strain exhibited similar growth characteristics with that of Ea strain, but its pathogenicity in mice was significantly lower than the latter one. The results above suggested that a naturally recombinant event might occur in the genome of HN-2019 strain between PRV classical strain and HB-98 vaccine strain, which will provide useful guideline for PRV vaccine design in the future.